THE LIBRARY IS PROVIDING INFORMATION SERVICES STUDYING THE NEEDS FOR INFORMATION RESOURCES (ART AND CULTURE BULLETIN, 2025)
This article discusses a number of problems arising in library activities and projects to address them.
Keywords: library activity; scientific and cultural development; reading; information technologies